Dietary Behaviors among Women with Osteoporosis at Merjan Teaching Hospital in Hilla City - ameen, wafaa; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2016)
Objectives: to assess Socio Demographic, Reproductive Characteristics, and healthy dietary behaviors. among women with osteoporosis . To determine the relationship between the socio demographic characteristics, reproductive data and dietary related behaviors. Methodology: A descriptive analytic design was conducted on Non- Probability ( purposive sample) of (90) women who have suffering from osteoporosis attend to (DEXADual-Energy X-ray Absorptiometry) unit in Merjan Teaching Hospital in Hilla City. A questionnaire has been used as a tool of data collection and consists of three part ;including : Socio Demographic, Reproductive Characteristics, and dietary behaviors, for the period of 9th of February to April 20th 2014.A pilot study has been carried out to test the reliability of the questionnaire and content validity has been carried out through the (19)experts. Descriptive and inferential statistical analyses are used to analyze the data . Results: The results of the study reveal that (36.7%) of women aged (50 - 59) years with Mean ± SD(52.46 ± 11.70),(44.4%) were not read and write ; Not employed were(74.4%); (60%)their resident in urban; (52.2%) low socio economic status , (22.2%) were in overweight and (60%) obese in different classes. And concerning reproductive information (58.9%)their age of menarche (11-12) years , (49.3%) their age at menopause (45-49)years,( 36.6%)having (7-9)times of pregnancy, (39%)having (4-6) time of deliveries and (67.1%) with breast feeding and (53.7%) use hormonal contraceptive. . There is significant relationship P≤ 0.05 between dietary behaviors and socio demographic characteristics in women occupation and socio economic status. Recommendations: Implement educational programs as early as in adolescence to obtain peak bone mass, health education to all women about the osteoporosis and its prevention through nutrition and exercise, and encourage the women who has any risk factors or at age of 50 years old to do Dexa examination .